Perspective pragmatique sur l’anaphore - Jean Albrespit (Corela)
The aim of linguistic pragmatics is the study of how meaning is computed in inferences and implicatures and what effects speech acts and presuppositions may have. One of the topics which received particular attention from researchers in pragmatics is anaphora and deixis. The corpus under consideration shows interesting occurrences of anaphora for a pragmatic analysis: the speaker must convince his audience and keep their attention. He tries to relate to them by referring to a “common ground” while at the same time delivering a coherent and structured speech. The starting point of this paper is the hypothesis that anaphora can only be analysed at text level and must incorporate such features as discourse cohesion, semantics, pragmatics and stylistics.